Psychosocial Intervention and Clinical/Educational Outcomes for Students with Emotional and Behavioral Disorders: An Evaluation of the Astor Transitions Program. Issue 45 (8th August 2019) - Whaley, Arthur L.; DiMotta, Rodney J.; Walker, Jurine; Santana, Michelle
Abstract: The Astor Transitions Program (ATP) was developed to assist youth with emotional and behavioral disorders moving into a new educational environment where the services would often be less integrated. A research/evaluation consultant was hired to conduct a program evaluation of the ATP. The study sample consists of the charts of 150 consecutive students admitted to ATP between April 2010 and March 2013. The following hypothesis was tested: the ATP service in terms of caseworkers' contacts will be associated with better clinical and educational outcomes. The major findings were the impact of caseworker contacts on clinical outcomes was indirect and greatest on type of placement; caseworker contacts had no effect on school attendance, yet ATP students were present about 85% of the time; and casework activity increased for chronic cases in placement but decreased after hospitalization. Recommendations were made to program staff on how to improve ATP services.